A green economy? - Simons, Petrus (Koers, 2014)
Economic growth has become a fetish, as it is believed to yield many benefits to society. It has its origins in the Enlightenment ideal of progress through science, technology and a free market economy. J.W. Goethe anticipated the problems of such progress in his poem Faust, especially its second part. Binswanger interprets Goethe’s view on the modern economy as a form of alchemy, an attempt to master time through the invention of monetary capital. Keynes’s views on progress and liquidity are compatible with this analysis. The problems, evoked by the uncritical application of scientific technology so as to increase material welfare, have given rise to a dialectic between business seeking growth and those concerned about its effects, especially on ecology. Sustainable development is an outcome of this dialectic, without abandoning it. Others, particularly those advocating décroissance [de-growth], reject the concepts underlying growth. The ideology underlying this is a combination of technicism and economism. A spiritual revolution is called for to break the hold of this ideology on society, with a change from the metaphor of the world as a machine to that of a garden-city. It is suggested that working groups should analyse the various proposals for change from the perspective of the garden-city metaphor.